Edukasi Pengetahuan Pajak Bagi Santri Di Pondok Pesantren Mamba'ul Ma'arif Jombang - Dwi Ermayanti Susilo; Wisnu Mahendri; Ahmad Bihar Isyqi; Ina Nikmatul Chasanah; Liya Rizkiyah (Forum Kerjasama Pendidikan Tinggi, 2023)
This service activity was carried out at the Mamba'ul Ma'afif Islamic boarding school Denanyar Jombang where this activity included the socialization of an understanding of tax education, benefits and how to pay taxes. The purpose of this community service activity is so that the students know and are used to helping convey to the surrounding community, among other things, the function of taxes for state development and how the process of paying taxes is. This service activity was carried out using the method of socializing tax education and holding quizzes about taxes to measure the level of knowledge of grade 3 students. The results of this activity based on observations, the socialization process and the results of the tax quiz turned out that many class 3 students were very enthusiastic about participating in the activity. This can be seen from the achievements of this community service activity that the service program which is a form of strategic action on tax introduction to increase awareness of tax inclusion and conduct tax awareness literacy for the students of the Mamba'ul Islamic boarding school is very important because as we know today, there are many people who still don't understand about taxes and are also not happy with taxes, in fact they just don't know about the benefits of taxes and what can be obtained from paying them. Therefore knowledge about taxes is needed from an early age to fortify society from bad and wrong tax stereotypes. This kind of provision can be started from the family, school and community environment.